2005
DOI: 10.1099/mic.0.27554-0
|View full text |Cite
|
Sign up to set email alerts
|

A unique nine-gene comY operon in Streptococcus mutans

Abstract: Many Gram-positive and Gram-negative bacteria possess natural competence mechanisms for DNA capture and internalization. In Bacillus subtilis, natural competence is absolutely dependent upon the presence of a seven-gene operon known as the comG operon (comGA-G). In species of Streptococcus, this function has been described for a four-gene operon (comYA-D in Streptococcus gordonii and cglA-D in Streptococcus pneumoniae). In this study, a nine-orf operon (named comYA-I) required for natural competence in Strepto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(60 citation statements)
references
References 41 publications
2
58
0
Order By: Relevance
“…This has been demonstrated for S. mutans and is consistent with the findings of the present study (47). An influence on expression of late competence genes was also found in LuxS mutants of S. pneumonia (22,62); however, in those studies the direct influence of AI-2 was not investigated.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…This has been demonstrated for S. mutans and is consistent with the findings of the present study (47). An influence on expression of late competence genes was also found in LuxS mutants of S. pneumonia (22,62); however, in those studies the direct influence of AI-2 was not investigated.…”
Section: Discussionsupporting
confidence: 82%
“…Subsequently, the cultures were allowed to grow for an additional 2 h and were then plated on BHI agar supplemented with tetracycline (5 g ml ÏȘ1 ) as well as on nonselective BHI plates. Transformation efficiency was defined as the ratio of transformants/total viable cells (47).…”
Section: Strains and Plasmidsmentioning
confidence: 99%
“…While there are numerous examples of mutations that lower the natural competence ability of S. mutans (Abranches et al, 2006;Ahn et al, 2005;Hussain et al, 2006;Merritt et al, 2005c;Qi et al, 2004;Rolerson et al, 2006;Senadheera et al, 2005Senadheera et al, , 2007Wang & Kuramitsu, 2006;Wen et al, 2005), to our knowledge, there is only one other report of a mutation that increases natural competence (Tao et al, 1993). This mutation was generated by chemical mutagenesis and its identity has, so far, not been published.…”
Section: Discussionmentioning
confidence: 91%
“…Determination of natural transformation efficiency was performed using a method similar to that described previously (Li et al, 2001;Merritt et al, 2005c). UA140 and the various hdrR and hdrM mutants were grown anaerobically to OD 600 0.2-0.3 in TH broth supplemented with 0.4 %, w/v, BSA.…”
Section: Introductionmentioning
confidence: 99%
“…To confirm these results, we examined two late competence genes, comYA and comX (Merritt et al, 2005), an early competence gene, comE, and its controlled bacteriocin-producing and immunity genes, nlmC (SMU.1914) and immA (SMU.1913), by real-time qRT-PCR. The results showed that, similar to the microarray data, comYA and comX were indeed downregulated at pH 5.5, but comE and the two bacteriocin-related genes were upregulated at this pH (Table 2).…”
Section: Downregulated Genesmentioning
confidence: 99%